2009
DOI: 10.1666/08-181.1
|View full text |Cite
|
Sign up to set email alerts
|

Cephalopods and paleoenvironments of the Fort Cassin Formation (upper Lower Ordovician), eastern New York and adjacent Vermont

Abstract: The dramatic late Early Ordovician radiation of cephalopods on tropical paleocontinents is illustrated by the diverse fauna (21 genera, 30 species) of the Fort Cassin Formation (Floian and lower Blackhillsian Stage) in northeast Laurentia. Cephalopods occur through the thin (ca. 30–65 m) depositional sequence of the Fort Cassin but are most common and diverse in mollusk-rich, trilobite-poor parts of the formation that characterize the thrombolite-bearing intervals in the shoaling part of the highstand systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…These conditions lasted without significant interruptions over a comparatively long time interval of around 5 million years. Additionally, compared with a similar long time interval in Early Ordovician shallow water reefs (Kröger & Landing ), the evolutionary changes within the cephalopod fauna were minimal during the growth of the Boda mounds.…”
Section: Conclusion and Summarymentioning
confidence: 84%
See 1 more Smart Citation
“…These conditions lasted without significant interruptions over a comparatively long time interval of around 5 million years. Additionally, compared with a similar long time interval in Early Ordovician shallow water reefs (Kröger & Landing ), the evolutionary changes within the cephalopod fauna were minimal during the growth of the Boda mounds.…”
Section: Conclusion and Summarymentioning
confidence: 84%
“…The taxonomic distinctness tripled throughout the entire Beekmantown Group and reached a maximum value in the Fort Cassin Formation of 3.67 (Kröger & Landing ). This value is nearly identical to that of the Boda Limestone cephalopods (Table ).…”
Section: The Boda Mound Cephalopod Fauna and The Ordovician Radiationmentioning
confidence: 99%
“…# without specimens from St. Chinian, * raw data are from Kraeger and Landing (2009 Table 2. Number of specimens collected from the St. Chinian, La Maurerie, and Foulon formations (Faunizones E/F, H, K respectively) from different localities of the Montagne Noire, France.…”
Section: St Chinian Formationmentioning
confidence: 99%
“…In emending the Baltoceratidae and restricting the family to Orthocerida taxa similar to Cochlioceras Eichwald, 1860, Kraeger et al (2007) excluded those genera possessing concave siphuncular segments with thickened connecting rings such as Rioceras Flower, 1964 originally included in the Baltoceratidae by Flower (1964). Similarly, revision of Protocycloceras lamarcki (Billings, 1859) by Kraeger & Landing (2009) has restricted the Protocycloceratidae to rod-bearing, annulate longicones of the Ellesmerocerida with concave siphuncular segments. As a consequence of these more restricted diagnoses Kraeger & Landing (2009) indicated that the remainder of the original Baltoceratidae were orphaned and the erection of a new higher taxon was required.…”
Section: Type Genus Rioceras Flower 1964mentioning
confidence: 99%
“…N ¼ number of specimens; S ¼ number of species; S rarified rarified S with census 55 specimens, lower and upper 95 % confidence interval in parentheses; J ¼ H 0 =log ðSÞ; where H 0 is the Shannon -Wiener index of the sample. # without specimens from St. Chinian, * raw data are from Kraeger and Landing (2009…”
Section: Faunal Composition and Depositional Settingmentioning
confidence: 99%